Behavioral Characteristics during Dental Treatment in Children with Autistic Spectrum Disorder Who Can Wear Clothes by Themselves - OGASAWARA, Tadashi; MAKII, Kakuma; YOKOTA, Makoto; MOCHIZUKI, Noriyasu; OKADA, Hisanori (Journal of the Japanese Society for Disability and Oral Health, 2019)
The behavioral characteristics in each dental scene of children with autistic spectrum disorder （ASD） who can remove and put on their clothes independently have not been clarified. Therefore, we examined behavioral characteristics and their factors.Dental treatment was divided into 12 scenes for 16 ASD children and 40 regular developmental children, and decision tree analysis was used to examine the behavior of 12 scenes：“Adaptation：Cooperative from beginning to end”, “somewhat incompatible”. The subjects were evaluated as “persons who moved or talked but did not disturb the medical treatment” and “non-adaptation：There was rejection behavior and the medical treatment was hindered”.“Indications” were significantly lower at 87.5% and 6.2% for children with typical development （p＜0.01）, and 87.5% of children with ASD were able to perform dental treatment under infiltration anesthesia. In all the scenes, the ASD children in the scene adaptation group were significantly less in number than those with regular development （p＜0.01）, and the three scene adaptations of “sit on the clinic table”, “opening instruction”, and “intraoral examination”. It is suggested that the factor may be adaptive if the developmental age of movement is 4 years and 6 months or more. The characteristic of ASD is related to adaptability：“it is supine,” （visual aid）, “surface anesthesia application”, “waiting time for surface anesthesia”, “infiltration anesthesia”, “waiting time for infiltration anesthesia”, “dental treatment”, and “return to sitting position”. Although it was found that a characteristic of ASD children is the presence of maladaptive behavior, it was suggested that dental treatment in the area is possible because it does not lead to the hindrance of medical treatment.